"There was something almost crude about it all…" – reading Crime and Punishment's epilogue hard against the grain. Issue 2 (2nd April 2020) - Naiman, Eric
ABSTRACT: This article employs a strategy of "adversarial reading, " seeking to find complexity and contradiction in the seemingly monologic epilogue to Crime and Punishment . Since the novel's most resistant and perverse interpreters, and in particular Svidrigailov, have vanished from the text prior to the opening of the epilogue, it is the reader's challenge to carry forward these characters' approach to textual interpretation and keep alive the novel's rejection of transparent, perfectly adequate denotation. Heuristically, this article asks what readers might find in the epilogue if they refuse to remain the passive recipients of Sonia's word.